BIOCOMPATIBLE NANO-COMPOSITE FROM CRAB SHELL WASTE: PREPARATION, CHARACTERIZATION AND THEIR POSSIBLE APPLICATION - RADHIKA RAJASREE S.R.; GAYATHRI S (International Journal of Pharma and Bio Sciences, 2014)
Chitosan which is known to have multiple functional properties has created significant interest among the researchers due to their biological activities and applications in the food, pharmaceutical and agricultural industries. Chitin and chitosan are the second most available biopolymer after cellulose. The present study was designed to evaluate the alternative uses for seafood wastes that are economically feasible. In the present work, extraction of crude chitosan using strong acids and one-step extraction of chitosan by co-fermentation with Lactobacillus sps.from red crab shell waste were tried. To achieve demineralization of crab shell waste by chemical and biological treatments, hydrochloric acid and lactic acid bacterium were applied. The pH decreased from 6.17 to 5.49 and from 6.12 to 5.29 at day 7 respectively. The study also deals with, the preparation, characterization and dye adsorption properties of novel biocompatible composite (Chitosan–zinc oxide nanoparticle) (CS/n-ZnO) were investigated. Two textile dyes, Coomassie Brilliant Blue and Acid Blue, were used as model compounds. The effect of CS/n-ZnO doses, initial dye concentration, and pH were elucidated. The results showed that the CS/n-ZnO being a biocompatible, eco-friendly and lowcost adsorbent that can be used for the adsorbtion of dye from colored solution.